Interactive Machine Learning Chatbot: Developing a Self-Learning Conversational bot using Python for Dynamic Knowledge Management - Kannan, K Nattar; Vijayaragavan, P.; Jaini, Santosh; Katikireddi, Phani Monogya; Balasundaram, N.; T, Chidananda (International Conference on Computing, Communication and Automation (Online), 2024)
Ensuring access to legal information and services is critical for justice and empowerment, particularly for economically disadvantaged individuals who often encounter obstacles in navigating the legal system. This study introduces an advanced chatbot developed using Python and the Natural Language Toolkit (nltk), designed to learn and improve from user interactions. Utilizing sophisticated pattern-matching algorithms and natural language processing (NLP) techniques, the chatbot effectively understands user queries and provides precise legal information. By integrating current government acts and legal regulations into its knowledge base, the chatbot ensures the delivery of accurate and up-to-date legal advice.